NATURAL HISTORY OF DUCTAL CARCINOMA IN SITU - Freitas-Junior, Ruffo; Lemos, Nayara Alves de Freitas; Moreira, Marise Amaral Rebouças; Rodrigues, Fábio Francisco Oliveira (Mastology, 2018)
Ductal carcinoma in situ (DCIS) has been detected more frequently in the last decades using the mammographic screening. The objective of the present study was to review the epidemiological aspects of DCIS. A bibliographic narrative review was carried out focusing on the following aspects: the epidemiology of DCIS to discuss subtypes; natural history; screening; and survival. It was possible to verify that the DCIS is currently considered a precursor lesion of breast cancer, presenting a considerable and uneven increased incidence between developed and developing countries, probably due to the inclusion of mammographic screening programs. There are controversies regarding the benefit or not of its detection, diagnosis, treatment and survival of patients with DCIS. It is concluded that the considerable increase in the incidence of DCIS raises an important discussion about the real need for its diagnosis as well as its real biological significance.